A questionnaire study of the negative outcomes for UK health professional volunteers in low and middle income countries. Issue 6 (15th June 2020) - Tyler, Natasha; Ackers, Helen Louise; Ahmed, Anya; Byrne, Ged; Byrne-Davis, Lucie
Abstract : Introduction: Past research has reported considerable benefits of international health professional volunteering for British healthcare professionals; however, there are also some negative outcomes reported. Negative outcomes reportedly happen on a personal, professional and organisational level. However, there is little evidence of the frequency they might occur. Methods: We aimed to understand what the negative outcomes of health professional volunteering in low-income and middle-income countries were, and how frequently they occurred, in an opportunistic sample of UK health professionals. We used a questionnaire developed using potential negative outcomes reported in the peer-reviewed papers. We conducted secondary analysis on cross-sectional questionnaire data from 222 healthcare professionals. Results: This research provides an indication of the frequency that negative outcomes might occur. Post hoc analyses revealed that some outcomes were experienced by the majority of health professional volunteers, for example, lack of formal recognition (131/169, 78%) and financial cost (92/169, 68%). While others happened less, for example, a reliance on agency or locum work (12/169, 7%) and loss of pension (31/169, 18%). Conclusion: The outcomes reported in this research quantify some of the concerns that have been raised in previous literature. Negative outcomes might be associated with certain features of volunteering and further research is needed to prospectively compare different features. Organisers of volunteering opportunities should be aware of the potential negative outcomes and engage with the research into negative outcomes to generate and apply findings about minimising potential negative outcomes, carefully balancing these against the needs of the host country.